Circular dichroism of rhodopsins and porphyropsins - Parkes, John H.; Rockey, John H.; Liebman, Paul A. (Biochimica et biophysica acta, 1976)
Circular dichroism and absorption spectra were determined for digitonin extracts of three rhodopsins: cattle, grass frog, and pigeon; and three porphyropsins: channel catfish, bluegill sunfish, and redear sunfish. A comparison of these spectra shows the following: (1) Porphyropsins, like rhodopsins, exhibit two positive CD peaks in the spectral region 321–700 nm: an α peak at about 520 nm and a small β peak at about 355 nm. These peaks substantially diminish upon bleaching. (2) In the CD spectra the α peaks of the porphyropsins are larger than the α peaks of the rhodopsins, while the β peaks are smaller than those of the rhodopsins. This is just the opposite of the corresponding relationship between the peaks in the absorption spectra. (3) The maxima of these peaks in the CD spectra of rhodopsins and porphyropsins are consistently blue-shifted from the corresponding maxima in absorption spectra. (4) Some of the visual pigments show additional positive CD peaks in the spectral region 250–320 nm. In all the visual pigments studied, the CD spectra in this region decrease on bleaching. No reciprocal relationship is observed between any of the CD bands in the visible and near ultraviolet region of the spectrum.